(untitled) (Communication & Society, 2020)
On June 1, 2019, Nayib Bukele assumed the presidency of the Republic of El Salvador, becoming the youngest leader in the democratic history of this Central American country. His communications strategy on Twitter attracted the attention of the international press, because of a peculiar way of using this tool to tweet direct orders to his governmental team through Twitter, with many of his messages having a humoristic lilt. Observing this way of communicating prompted a wish to investigate the communications strategy of President Nayib Bukele on Twitter. Online tools, such as Twitonomy and Vicinitas, were used for the quantitative analysis of the account over the first two weeks of his presidency. Additionally, an in-depth interview was held with the communications secretary of the government of El Salvador, Sofía Medina. Finally, a broad description of the economic and social situation of the country helps understand the relevance of the data obtained from the analysis, emphasizing the scarce access to both information technology and social networks among the inhabitants.